Morphological justification of laparoscopic transabdominal preperitoneal (TAPP) operation for the inguinal hernia recurrence - Feleshtynskyi, Y. P.; Shtaier, A. A. (Journal of Education, Health and Sport, 2020)
Introduction. The frequency of the inguinal hernia of the repeated recurrences is up from 9,3 to 12%. In surgical treatment re-fixation of the mesh to the atrophied tissues of the inguinal canal is unreliable. The posterior access can be much more reliable for the patients, in which the mesh will be fixed to the unchanged muscular-aponeurotic tissues of the inguinal area. Aim. To increase the efficiency of recurrent inguinal hernias surgical treatment by justification of using the TAPP surgical technology. Materials and methods. An analysis was made in the clinic Kiev City Clinical Hospital No. 5. about surgical treatment of recurrent inguinal hernias in 105 patients. Surgical operations were also divided. The patients were divided into 2 groups, the first group (52), where the Liechtenstein’s operation was repeated, and the second group of the patients (53) were confirmed by TAPP (patent No. 1299.1 from 26.11.18). A biopsy of the inguinal muscle aponeurotic tissues was made during surgery in both groups of the patients. Also morphological examination was made. For a final comparison of the morphological examination of inguinal tissues, a biopsy was performed in 20 patients who had an appendectomy. Results and discussions. In I group to the remote period in 8 (16%) patients there were chronic inguinal pain and recurrence of hernia was observed in 4 (8%) patients. In II group long-term results were as follows, chronic inguinal pain was diagnosed in 2 (4%) patients, recurrence was observed in 1 (2%) patient. After making a morphological comparison of the three groups, it was found that in group I were signs of severe chronic inflammation with the formation of granulation of the tissue, scar tissue, destruction of elastic fibers, both in the tissue of the anterior abdominal wall and in the wall of the vascular component. The morphological picture of the II and III groups are similar, with weakly expressed chronic inflammatory infiltration, with savings of the elastic fibers and less degenerative changes. Conclusion. The morphological reasoning of the use of improved TAPP was the absence of atrophic changes in the muscular-aponeurotic tissues of the inguinal region, while in Liechtenstein’s second operation there was atrophy, scarring of inguinal tissues, so fixation of the mesh to such tissues can leads to recurrence.